2015
DOI: 10.1002/cam4.605
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment of complex located pediatric low‐grade gliomas using iodine‐125 brachytherapy alone or in combination with microsurgery

Abstract: To analyze efficacy, functional outcome, and treatment toxicity of low‐dose rate I‐125 brachytherapy (SBT) alone or in combination with best safe resection (in case of larger tumor volumes) as first‐line treatment for pediatric low‐grade gliomas (PLGGs) not suitable for complete resection. Consecutively treated (2000–2014) complex located circumscribed WHO grade I/II PLGGs were included. For small tumors (≤4 cm in diameter) SBT alone was performed; for larger tumors best safe resection and subsequent SBT was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The considered patients were treated with 50-65 Gy cumulative therapeutic dose delivered within 9 months. Kunz et al [96] reported similar results in a clinical study performed on 58 pediatric patients. SBT alone was performed on patients with LGG of ≤ 4 cm in diameter.…”
Section: Brachytherapy Dosimetry In Pediatric Therapy Applicationssupporting
confidence: 52%
See 1 more Smart Citation
“…The considered patients were treated with 50-65 Gy cumulative therapeutic dose delivered within 9 months. Kunz et al [96] reported similar results in a clinical study performed on 58 pediatric patients. SBT alone was performed on patients with LGG of ≤ 4 cm in diameter.…”
Section: Brachytherapy Dosimetry In Pediatric Therapy Applicationssupporting
confidence: 52%
“…Clinical Experience With BT in Pediatrics: The largest clinical experience with BT in pediatrics has been reported for soft-tissue sarcoma [94], [97], [99], [100]. Furthermore, clinical trials on patients with solid tumors [95], lowgrade gliomas [96], [101], and genital cancer-for both male [93] and female [98] pediatric populations-have been published. Merchant et al [99] have reported on the treatment of soft-tissue sarcoma with BT alone or as boost to EBRT.…”
Section: Brachytherapy Dosimetry In Pediatric Therapy Applicationsmentioning
confidence: 99%
“…Currently glioma treatments have shown low effectiveness for the outcome of patients with glioma, which have emphasized the need for new molecularly targeted therapies ( 11 , 13 ). Gliomas are aggressive and their incidence rate in patients is increasing, resulting in a relative high mortality rate ( 13 , 14 ). Previous reports have suggested that TUN may have crucial roles in inhibiting tumor growth and enhancing apoptosis mediated by tumor necrosis factor-related ligands ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the antiglioma therapies, including chemoradiotherapy and biotherapy are efficient for patients with cancer (17,18). Incidence rates of gliomas are increasing (19,20). Evidence suggests that tunicamycin may inhibit tumor growth and promote apoptosis mediated by tumor necrosis factor-related apoptosis-inducing ligand (10,21).…”
Section: Discussionmentioning
confidence: 99%